Sistem Manajemen Krisis dalam Meningkatkan Penegakan Integritas di Badan Pemeriksa Keuangan RI - Rifaldi Kelana; Bahrullah Akbar; Faria Ruhana (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the efforts of the Audit Board of the Republic of Indonesia (BPK RI) in preventing and addressing integrity crises through value enforcement, violation prevention, and the development of a crisis management system. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis. The main findings indicate that BPK RI has established instruments for strengthening integrity. However, challenges remain in terms of oversight and the dissemination of ethical values. Integrity enforcement has been carried out through exemplary leadership and firm sanctions. Meanwhile, the crisis management system has not yet been formally structured. It is recommended that BPK RI develop a comprehensive crisis management system, strengthen the culture of integrity, and enhance ethical leadership and post-crisis evaluation to build a resilient and adaptive organization.